2018
DOI: 10.1063/1.5041867
|View full text |Cite
|
Sign up to set email alerts
|

Research on the selective adhesion characteristics of polydimethylsiloxane layer

Abstract: Polydimethylsiloxane (PDMS) is a widely used inexpensive, non-toxic material which has many advantages. But it is generally considered that PDMS does not adhere to the other substrates without the special treatments due to its low surface energy. However, in this paper, it is the first time that we found that the PDMS adhered on the silicon dioxide substrate to form an adhesive layer only by the routine cast molding process. The mechanism of the PDMS adhesion on the silicon dioxide substrate during the process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…A PDMS post treatment is added to the silver coated samples to improve the ultrasonic bleach wash durability. PDMS is a low surface energy polymer that offers liquid repellent and chemical resistance properties to fabrics [ 45 ]. Both PET-NP and PET-Ink samples are dipped in PDMS (1:10 curing agent:PDMS ratio, Sylgard 184) dissolved in hexane and cured in an oven at 150°C for two hours to make PET-NP/P and PET-I/P samples, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…A PDMS post treatment is added to the silver coated samples to improve the ultrasonic bleach wash durability. PDMS is a low surface energy polymer that offers liquid repellent and chemical resistance properties to fabrics [ 45 ]. Both PET-NP and PET-Ink samples are dipped in PDMS (1:10 curing agent:PDMS ratio, Sylgard 184) dissolved in hexane and cured in an oven at 150°C for two hours to make PET-NP/P and PET-I/P samples, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In the plasma treatment process, there is only a small amount of hydroxyl groups (the inherent hydroxyl groups) on the surfaces of PDMS and silicon dioxide layer. Xiangdong et al mentioned that the contact of such two surfaces will produce a small amount of Si-O-Si bonds, which can only form a week adhesion force [ 55 ]. Thermal annealing is another method used to improve adhesion performance.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the coated group showed a significantly higher contact angle than the noncoated group, thereby indicating a lower surface energy of the coated specimens than that of the noncoated specimens. This is due to the hydrophobicity and low surface energy of PDMS, which is a beneficial feature of the material that contributes to the low bacterial adhesion [ 40 ].…”
Section: Discussionmentioning
confidence: 99%